The Rubble of Culture - Collings, David A. (CCC2 Irreversibility, 2023)
Humanity now faces the possibility that it will become extinct over the next few decades or so. This is not simply a reality about the biological fate of the species; it also raises the prospect of thought’s own extinction. But what does it mean for thought that it, too, might disappear?